Adverbs In Expressions of Disagreement: a Corpus Study - Mutiara, Rika (Fakultas Adab and Humaniora, Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2018)
This study examined the occurrences of expressions of disagreement in the textbook and corpora namely Corpus of Contemporary American English (COCA) and British National Corpus (BNC). Besides, this study scrutinized the concordance lines in which disagreement occur to obtain other language functions that were usually used together in expressions of disagreement. It also studied the used of adverbs in expressions of disagreement. They were categorized based on semantic categories develop by Biber, et al. (1999). Some expressions of disagreement given in the textbook were not found in BNC. The findings from the corpora showed that the speakers tend to give opinions and reasons in stating disagreement. They, moreover, showed direct respect to the interlocutors in order to manage the relationship. These language functions were not found in the expressions of disagreement in the textbook. The adverbs that belonged to the categories of degree and stance were more salient than any other categories. The adverbs intensified the level of disagreement and represent speakers’ certainty. Furthermore, the adverbs indicate speakers’ attitude toward the issues of disagreement. It seemed that adverbs played a role in stating disagreement. However, no expressions of disagreement in the textbook contained adverbs.—Penelitian ini bertujuan untuk mengecek kemunculan ungkapan yang digunakan untuk menyatakan tidak setuju di buku teks dan korpus. Korpus tersebut adalah Corpus of Contemporary American English (COCA) dan British National Corpus (BNC). Selain itu, penelitian ini mengkaji ungkapan lain yang biasanya muncul ketika menyatakan tidak setuju dengan menganalisa baris konkordansi. Lebih dalam lagi, penelitian ini menganalisa adverbial yang muncul dalam ungkapan menyatakan tidak setuju. Adverbia dikategorikan berdasarkan klasifikasi yang dikembangkan oleh Biber, dkk (1999). Beberapa ungkapan yang muncul di buku teks tidak ditemukan di BNC. Penutur cenderung memberikan pendapat dan alasan ketika menyatakan tidak setuju. Mereka juga menunjukan sikap hormat kepada lawan bicaranya untuk menjaga hubungan. Hali seperti ini tidak ditemui di ungkapan menyatakan tidak setuju yang terdapat di buku teks. Adverbia yang berfungsi untuk menunjukan kadar dan kepastian dalam ungkapan tidak setuju merupakan fitur penting. Selain itu, adverbia yang merefleksikan sikap penutur juga menjadi fitur yang menonjol dalam menyatakan tidak setuju. Hal ini menunjukan bahwa adverbia memiliki peranan tersendiri ketika penutur menyatakan tidak setuju. Namun, semua ungkapan menyatakan tidak setuju di buku teks tidak memuat adverbia.DOI : 10.15408/bat.v24i1.7017